POLICI: A web application for visualising and extracting yellow fever vaccination coverage in Africa. Issue 11 (7th March 2019) - Hamlet, Arran; Jean, Kévin; Yactayo, Sergio; Benzler, Justus; Cibrelus, Laurence; Ferguson, Neil; Garske, Tini
Highlights: High levels heterogeneity in population-level vaccination coverage. Heterogeneity found within countries, across age groups and throughout time. POLICI interactively highlights past, present and future estimates of coverage. Understanding heterogeneities can guide resource efficient vaccination campaigns. Abstract: Recent yellow fever (YF) outbreaks have highlighted the increasing global risk of urban spread of the disease. In context of recurrent vaccine shortages, preventive vaccination activities require accurate estimates of existing population-level immunity. We present POLICI (POpulation-Level Immunization Coverage – Imperial), an interactive online tool for visualising and extracting YF vaccination coverage estimates in Africa. We calculated single year age-disaggregated sub-national population-level vaccination coverage for 1950–2050 across the African endemic zone by collating vaccination information and inputting it into a demographic model. This was then implemented on an open interactive web platform. POLICI interactively displays age-disaggregated, population-level vaccination coverages at the first subnational administrative level, through numerous downloadable and customisable visualisations. POLICI is available athttps://polici.shinyapps.io/yellow_fever_africa/ . POLICI offers an accessible platform for relevant stakeholders in global health to access and explore vaccination coverages. These estimates have already been used to inform the WHO strategy to Eliminate Yellow fever Epidemics (EYE).